2014
DOI: 10.1371/journal.pone.0096581
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telephone Support Interventions on Coronary Artery Disease (CAD) Patient Outcomes during Cardiac Rehabilitation: A Systematic Review and Meta-Analysis

Abstract: BackgroundCardiac rehabilitation is offered to individuals after cardiac events to aid recovery and reduce the likelihood of further cardiac illness. However, patient participation remains suboptimal and the provision of high quality care to an expanding population of patients with chronic heart conditions is becoming increasingly difficult. A systematic review and meta-analysis was conducted to determine the effect of telephone support interventions compared with standard post-discharge care on coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…(23) At the end, the researchers concluded that tele-nursing as a preventive method can cause improved glycemia of patients. (24) Also, the review study by Kotb et al (2014) testing the extent of compliance with treatment in patients with coronary artery disease, also confirmed the results of the present study. They found that telephone follow-up resulted in diminished rehospitalization of patients in hospital as well as reduced systolic blood pressure and depression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…(23) At the end, the researchers concluded that tele-nursing as a preventive method can cause improved glycemia of patients. (24) Also, the review study by Kotb et al (2014) testing the extent of compliance with treatment in patients with coronary artery disease, also confirmed the results of the present study. They found that telephone follow-up resulted in diminished rehospitalization of patients in hospital as well as reduced systolic blood pressure and depression.…”
Section: Discussionsupporting
confidence: 86%
“…They found that telephone follow-up resulted in diminished rehospitalization of patients in hospital as well as reduced systolic blood pressure and depression. (24) The results of a study by Behzad et al (2015) entitled the effect of empowerment program (self-care workshop) based on telephone follow-up (Tele-nursing) emphasized selfefficacy in promoting self-efficacy in self-care behaviours of the elderly with hypertension. (25) In the study by Boraz et al entitled "comparing the effect of in person and distance education of self-care on the quality of life and physical problems of patients undergoing haemodialysis maintenance therapy, they found that most of the studied variables including laboratory tests, blood pressure, weight gain between two sessions of dialysis, pruritus, oedema, and warmness of the vascular pathway in each of the groups of in person and distant education, changed significantly before and after the education.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that telephone-based health education during cardiac rehabilitation might improve all-cause hospitalisation, anxiety, depression, smoking cessation and systolic BP, but there is no evidence for improvements in all-cause mortality and reductions in low-density lipoprotein cholesterol. 59 …”
Section: Resultsmentioning
confidence: 99%
“…Telephone-based health education appeared to be effective for reducing hospitalisations, systolic BP, smoking rates, depression and anxiety. 59 The educational interventions for patients with ACS focused primarily on clinical outcomes (hospitalisation and mortality), modifiable risk factors (BP, low-density lipoprotein levels and smoking cessation) and other psychological outcomes (anxiety and depression).…”
Section: Discussionmentioning
confidence: 99%
“…New methods for outpatient secondary preventive follow-up have been called for, and the involvement of healthcare staff other than physicians, such as nurses and pharmacists, as well as new regimens of follow-up are recommended in the latest guidelines [ 5 ]. In small studies, telemedical methods have had interesting results in improving both adherence to medication and risk factors in the short-term [ 6 , 7 ]. A more effective secondary preventive strategy must be both cost effective and easily implemented in today’s health care systems, with applicability to a large part of the target population and flexibility to meet each individual´s needs.…”
Section: Introductionmentioning
confidence: 99%